Parecidos de familia: contenido e importancia de una idea de Wittgenstein = Family resemblances: content and importance of an idea of Wittgenstein - Fermandois, Eduardo 1963- (2022)
According to the main thesis of this article, in order to articulate the scope and interest of Wittgenstein’s family resemblances topic, we should see into it not an answer to the question what concepts in general are, but a methodological proposal. Two questions guide the central part of the text: (1) What does "family-resemblances concepts" mean? (2) What concepts fall within the corresponding class? Regarding (1) I try to show that "family-resemblances concepts" is not an unequivocal term: a first sense has to do with the dictum of "similarities overlapping and criss-crossing" (IF 67) and is to be distinguished from a second sense associated with the topic of "blurred edges" (IF 71). This distinction lies behind the answer I offer to (2): in the first sense of the term, there is no family concept at all, while according to the second sense all concepts are of this kind. In the final part I propose a reinterpretation of the issue from a methodological perspective. To say that concepts like language, understanding, thinking, etc. are family concepts means that the philosophical reflection on them should not centre on the praxis of looking for definitions. As important ―maybe more important― as that it’s the careful description of paradigmatic examples, as "centers of variation" (EPB 190).
Según la tesis principal de este artículo, para articular el alcance e interés del tema wittgensteineano de los parecidos de familia se requiere ver en él, no una respuesta a la pregunta por lo que sea un concepto en general, sino una propuesta de carácter metodológico. Dos preguntas orientan la parte central del texto: (1) ¿Qué significa "conceptos de parecidos de familia"? (2) ¿Cuáles serían los conceptos en cuestión? Con respecto a (1), intento mostrar que el término no es unívoco: un primer sentido dice relación con el dictum de los "parecidos que se superponen y entrecruzan" (IF 67) y se diferencia de un segundo sentido asociado al tema de los "bordes borrosos" (IF 71). Con apoyo en esta distinción ofrezco una respuesta a (2): en el primer sentido del término, no existe ningún concepto de familia, mientras que de acuerdo con el segundo todos los conceptos lo son. En la parte final propongo reinterpretar el tema en clave metodológica. Afirmar que conceptos como los de lenguaje, comprender, pensar, etc., son conceptos de familia significa que la reflexión filosófica sobre ellos no pasa fundamentalmente por buscar definiciones; que tanto o más importante es la cuidada descripción de ejemplos paradigmáticos, como "centros de variación" (EPB 190).
Keywords: Blurred edges; Bordes borrosos; Concept; Concepto; Definición; Definition; Ejemplos; Examples; Family resemblances; Filosofía; Game; Juego; Limit; Límite; Parecidos de familia; Philosophy